Efectividad De La Colecistectomía Laparoscópica Según Técnicas Francesa Y Americana En El Manejo De Colecistitis Aguda - Clínica San Gabriel Periodo 2011 - 2013. - Lozada Zelada, Edward Fernando (2014)
Objective: Determine whether laparoscopic cholecystectomy as French technique is more effective than the American technique in the surgical management of patients with acute cholecystitis. Material and Methods: This study is a retrospective comparative descriptive analytical study, information was collected from medical records it was analyzed using SPSS see. The sample consisted of 60 medical records for French technical and 60 medical records for all American art met the study inclusion criteria. Results: No record of any intraoperative complication was found. The average operative time operated with French T.: 56.97 minutes and Operated American T.: 63.20 minutes, p (0.21) in favor of the French technique. On perioperative complications of surgery with French T.: 6 patients (10%) had recurrent pain and operated with American T.: 7 patients (12%) had recurrent pain and 1 patient (3%) morbidity of the surgical wound and when compared these values using the test of proportions for qualitative variables no statistically significant difference was obtained. The average hospital stay of the patients operated on French T.: 1.62 days and Operated American T.: 1.88 days p not statistically significant (0.58) difference was obtained. No patients suffered death as a result of the surgical procedure. Conclusions: In the experience of the San Gabriel Clinical about the use of laparoscopic cholecystectomy according to French and American are equally effective, however, the French technique had shorter operating time.